Pengaruh Expressive Movement Music Therapy Dan Aromaterapi Lavender Terhadap Penururan Kecemasan Pada Wanita Akseptor KB Suntik - Ariyati, Ni Made (STIKES ADVAITA MEDIKA TABANAN, 2024)
Intoduction: Injectable birth control is a way to prevent pregnancy that is given by injecting hormones into the body. Problems that often arise when using injectable birth control are weight gain, amenorrhea, and anxiety when getting an injection. To reduce anxiety, non-pharmacological therapy is carried out, namely Expressive Movement Music Therapy and Lavender Aromatherapy. The aim of this research is to determine the effect of Expressive Movement Music Therapy and Lavender Aromatherapy on reducing anxiety in women receiving birth control injections. This research used a Pre Experiment research design with an Intact-Group Comparisons design with purposive sampling, with 40 respondents being injectable contraceptive acceptors who were divided into 2 groups, namely the treatment group and the control group. Anxiety was measured using the Numeric Rating Scale-Anxiety (NRS-A) questionnaire, then data analysis was carried out using Mann Whitney because the data was not normally distributed. Result: The results of the study showed that there were differences in the anxiety levels of injectable contraceptive acceptors in the treatment group after being given the intervention with a p-value in the post-test for the treatment group of 0.000<0.05 and the mean post-test value being 2.20, which means that the average respondent experienced mild anxiety. Analysis using Mann Whitney obtained a p value = 0.00, which is <0.05, so there is a significant influence between Expressive Movement Music Therapy and Lavender Aromatherapy on reducing anxiety in women receiving birth control injections